Pengaruh Market Capitalization (MC) terhadap Stock Price Pada Perusahaan Sektor Consumer Goods yang Terdaftar di BEI Periode 2018-2020 - Anita Bela Nathania; Vania Yulitasari Handoko; Yulius Jogi Christiawan (Business Accounting Review, 2020)
This study discusses the effect of market capitalization on stock prices. The sample used in this study are consumer goods sector companies listed on the IDX in the 2018-2020 period. In this study using one of the panel data regression analysis. This research method uses software-based statistics, namely Gretl (Gnu Regression, Econometrics, and Time-series Library). This study uses panel data. Panel data is a combination of time series data and cross-sectional data. This study also uses the control variables dividend per share (DPS), earnings per share (EPS) and book value per share (BVPS). The management of data samples as many as 62 companies in the consumer goods sector listed on the IDX during the 2018 - 2020 period and with a predetermined sampling technique, resulted in 32 companies. The final sample is 96 from the consumer goods sector that meets the purposive sampling criteria with observations from 2018-2020. The results show that market capitalization has a positive effect on stock prices. The control variable dividend per share (DPS) has a significant positive effect on stock prices, earnings per share (EPS), and book value per share (BVPS) has a negative effect on stock prices.